Morphological caste studies in the neotropical swarm-founding polistinae wasp Angiopolybia pattern (Lepeletier) (hymenoptera: Vespidae) - Gelin, Luiz F. F. [UNESP] (2008)
Neotropical swarm-founding wasps present polygynic colonies and a great variation in relation to caste differentiation, ranging from species in which queens and workers are similar in shape and size to those where variation in shape and size is conspicuous. Canonical discriminant analysis and Bonferroni t-test analysis on morphometric data collected from eight body parts of specimens from nine colonies of Angiopolybia pallens (Lepeletier) were undertaken as a step towards to a better understanding on caste differenciation in Epiponini. All specimens were dissected to verify the ovary developmental stage, and the spermatheca was removed to check for the mating status. Females were then grouped as queens (mated with developed ovaries), intermediates (virgin with developed ovaries) and workers (virgin with undeveloped ovaries). Even though differences were found for some measurements in seven out of the nine colonies evaluated, multivariate analysis (Wilks' lambda values) indicated castes could not be reliably distinguished only by morphology. We conclude that morphological differences among A. pallens castes are low or absent, reflecting a possible groundplan for the Epiponini, i.e. a post-imaginal pattern of caste differentiation.